A mixed methods study on the readiness of dental, medical, and nursing students for interprofessional learning. - Mitsuyuki Numasawa (Public Library of Science (PLoS), 2021)
Background Interprofessional education (IPE) is crucial in dentistry, medicine, and nursing. However, scant mixed methods studies have compared the IPE outcomes across these disciplines to develop evidence-based IPE. This study explored the differences in the readiness of dental, medical, and nursing students for interprofessional learning before and after IPE workshops and elucidated reasons for this disparity. Methods Data were obtained from dental, medical, and nursing students who participated in IPE workshops conducted at Tokyo Medical and Dental University in Japan in 2019 and 2020. The participants filled the validated Japanese version of the Readiness for Interprofessional Learning Scale (RIPLS) before and after attending the workshops (n = 378). Paired t-tests were performed to assess differences between the pre- and post- workshop RIPLS scores. Welch's t-tests were deployed to evaluate interdisciplinary differences in their scores. Qualitative analyses were conducted using an explanatory sequential design with focus group discussions (FGDs) held with 17 dental students to explain the quantitative results. Results Total RIPLS scores increased significantly for every discipline after the workshops (p < 0.001). Dental students scored significantly lower pre- and post- workshop aggregates than medical and nursing students, respectively (p < 0.001). The FGDs yielded three principal themes in the explanations tendered by dental students on their lower scores: 1) dental students rarely felt the need for interprofessional collaborations, 2) dentists often worked without the need for interprofessional collaborations, and 3) dental students believed their contribution to the workshop was insufficient. Conclusions The results revealed divergences in the readiness of dental, medical, and nursing students for interprofessional learning, and the study illuminated possible reasons for these disparities. These outcomes will help develop evidence-based IPE by indicating approaches to place a higher value on interprofessional collaborations in educational environments, ameliorate the awareness of educators, and enhance the workshop facilitation style.